2019
DOI: 10.32350/bsr.0101.01
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effects of Gamma Radiation (Cobalt-60) on the Shelf Life and Nutritional Quality of Carrot (Daucus Carota): A Review

Abstract: Carrot is recognized as a most nutritious vegetable since it contains essential nutrients, vitamins, fibers and minerals required for normal growth and development of all living beings. The quality of vegetables is affected during storage due to ethylene production, respiration, transpiration, growth, development, compositional changes, physiological breakdown, physical damage and pathological breakdown. Under optimal storage conditions carrots can be preserved for 6-8 months without affecting any quality attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Similar results were interpreted by Nunes et al (2011) and Shami and Naz (2019) as they observed that gamma doses of low levels were best to retain the quality of fresh-cut baby carrots. These observations are in corroboration which our present studies.…”
Section: Total Plate Count (Log 10 Cfu/ml)supporting
confidence: 86%
“…Similar results were interpreted by Nunes et al (2011) and Shami and Naz (2019) as they observed that gamma doses of low levels were best to retain the quality of fresh-cut baby carrots. These observations are in corroboration which our present studies.…”
Section: Total Plate Count (Log 10 Cfu/ml)supporting
confidence: 86%